(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The community service program focuses on strengthening the management of BUMDesa Bicak Makmur in Bicak Village, Mojokerto Regency, particularly in cost control and marketing of its flagship product, ecoprint. The main problems identified include the absence of a standardized financial recording system, low product quality due to limited technical skills, and insufficient utilization of digital marketing. To address these challenges, the program provided training on Excel-based accounting applications, digital marketing strategies, and ecoprint production techniques delivered by experienced practitioners to enhance product quality and competitiveness. The approach adopted is Participatory Action Research (PAR), developed by Kurt Lewin (1946), which emphasizes active collaboration between the service team and BUMDesa managers. The results show significant improvements in cost efficiency, accurate pricing, and increased confidence among managers in promoting their products online through platforms such as Shopee, Instagram, and TikTok, thereby expanding market reach both nationally and internationally.